Soap as a Product of the Food Industry in the Blockaded Leningrad: Production and Existence in 1941-1942 - Olga A. Gavrilova (RUDN Journal of Russian History)
The authors discuss the problems of functioning of soap factories in the conditions of the siege of Leningrad, representing the perfumery and cosmetics industry of the food industry. Attention is paid to the range of products manufactured by enterprises, the peculiarities of the raw material base. The conditions that provoked the decline in production, the deterioration of product quality and the narrowing of the range of manufactured goods have been studied. Attention is focused on the search for fat substitutes and the use of the company's equipment to open new areas of activity that take into account the circumstances of wartime. The interaction of the USSR Drug Food Industry and the special commission of the Council of People's Commissars of the USSR on food supply of Leningrad in connection with the supply of food raw materials and foodstuffs to the blockaded city is analyzed. The intention of the central government bodies to include household soap in shipments of food products to ensure timely card delivery to the population and replenishment of supplies has been revealed. And also to send railway trains with vegetable oil to Leningrad to create raw materials for soap-making enterprises. The article considers the practices of household detergents and attempts by the population to use soap as an exchange tool to expand the food ration. The features of personal hygiene of blockade runners in conditions of acute shortage of detergents and interruptions in the work of baths are characterized. The conclusion is made about the progressive difficulties in maintaining soap production in the conditions of the blockade of the city. Despite the efforts of the management of enterprises to find substitutes for raw materials and change technological processes, the complete exhaustion of even conditionally suitable materials for soap production could not allow the restoration of detergent production with the start of electricity supply to plants.